Pengembangan Media Bimbingan Karier Berbasis Android di SMK Negeri 1 Koto Besar - Laila Hidayati; Fahmi Rizal; Syahril Syahril (Universitas Negeri Padang, 2021)
This research is motivated by the need for career guidance services that cannot be implemented optimally because the media for the implementation of Career Guidance is not yet available. In addition, students are also less interested in carrying out career guidance so that the provision of motivation and career information to students has not been carried out properly. Career Guidance Services are needed by students who are currently unstable teenagers in determining their own careers. So that BK teachers need interesting and flexible media in their use to be used during the Career Guidance service process. The purpose of this research is to develop android-based media to assist the implementation of Career Guidance to make it more practical, effective and interesting, thereby increasing students' understanding and strengthening in choosing careers independently. This study uses the Research and Development (R&D) 4D model. The research was carried out at SMKN 1 Koto Besar with the research subject of class XI Kimia Industri, totaling 40 students. Data collection instruments consist of observations, interviews and questionnaires. Data analysis technique for validity test uses Aikens's V formula, practicality test uses descriptive statistics, and effectiveness test uses level categorization. The results showed that the android-based career guidance media was practical and effective. This can be seen from the practicality test given to teachers and students with the results